Teachers’ Perception of Collaborative Learning in English Speaking Class Program: A Case Study - Tri Setiani; Yuyun Yulia (Universitas Islam Negeri Palopo, 2025)
This study investigates the perceptions of English and non-English background teachers regarding the implementation of collaborative learning in an English-Speaking Class program to improve speaking skills among non-English background teachers. The program ran over a year at an Islamic Boarding Secondary School in South Sumatra. Using a qualitative case study design, the data were gathered through questionnaire and focus group discussions with 23 non-English background teachers and 4 English teachers. The findings indicated that most of participants found collaborative learning effective to be used for enhancing participants’ engagement and communication skills. Both English and non-English teachers also noted the positive impact of peer interaction on boosting student confidence and motivation. However, challenges of this program such as unequal participation, fluctuating motivation, scheduling time constraint, and lack of structured teaching materials were noted. Despite these challenges, English teachers emphasized that collaborative learning could significantly benefit language learners with an appropriate scaffolding and task alignment. The study indicates that while collaborative learning is a suitable and effective method for adult learners, proper program planning and continued support are required to overcome the challenges. Future study recommends in exploring the strategy to enhance consistency of participation, increase motivation, and determine the long-term impact of collaborative learning on teachers' language ability and pedagogy.